Natural radioactivity in reservoir sediment near an industrial park of northwest China. (28th April 2016) - Lu, Xinwei; Pan, Huiyun; Ren, Chunhui; Yang, Linna
Abstract: The activity concentration of natural radionuclides in the sediment of a reservoir near an industrial park of northwest China was determined using gamma ray spectrometry. The activity concentrations of 226 Ra, 232 Th and 40 K in the investigated samples range from 30.2 to 37.5, 56.5 to 79.8 and 785.6 to 940.3 Bq kg −1 with an average of 33.2, 71.8 and 866.2 Bq kg −1, respectively, which are higher than the corresponding activity concentrations in the control sample. Radium equivalent activity, external hazard index, internal hazard index, indoor air absorbed dose rate and annual effective dose rate were calculated to assess the radiation hazards associated with the use of this sediment in the construction of dwellings. It was concluded that the radiation levels in the reservoir sediment do not give rise to radiological health concerns and the sediment can be safely used in the construction of buildings.